CONTRIBUTION OF THE SALAFIYAH ISLAMIC BOARDING SCHOOL EDUCATION SYSTEM IN BANTEN INTO FORMING THE PERSONALITY OF ISLAMIC STUDENTS - Khairul, Agus; Syarifudin, Encep; Firdaos, Rijal (Yayasan Education and Social Center, 2024)
This research analyzes the contribution of the Salafiyah Islamic Boarding School education system in Banten in shaping the students' personalities. Two research methods were used: library research and field research. Library research involves collecting relevant theories and writings, while field research is carried out by direct observation at the research location. The research results show that the Salafiyah Islamic Boarding School in Banten has an important role in instilling moral education in students. The Islamic boarding school tradition is a reflection of the vision and mission of the institution, with moral educational values ​​internalized by the students. The learning system based on the Compassion System (SKS) has succeeded in forming students who obey the rules and are able to adapt to the Islamic boarding school environment and society. Islamic boarding school education in Banten is considered an effective means for parents to shape behavior that is in accordance with religious and social values. Even though it is faced with the challenges of modernization, Islamic boarding school education remains relevant in shaping good moral behavior through religious activities and the rules that are applied. However, there are still certain behavioral deviations in Islamic boarding schools. However, the formation of students' personalities is maintained through the values ​​of family, togetherness, helpfulness, honesty and responsibility. The centralized role of kiai as role models, as well as community support in various forms, also supports the existence and development of Salafi Islamic boarding schools amidst challenges and threats from both internal and external sources